2007
DOI: 10.1080/02705060.2007.9664154
|View full text |Cite
|
Sign up to set email alerts
|

Epipelic and Epilithic Diatoms of the Balikli Spa in Central Anatolia, Turkey

Abstract: The epipelic and epilithic diatoms of Balikli Spa were investigated during April and May 2003. Species of the genera Cymbella, Amphora and Gomphonema constituted the main groups, and Cymbella cymbiformis and Gomphonema olivaceum were the dominant species. Species belonging to genera Navicula and Acnanthes were less in variety. Most diatom species, with the exception of Fragilaria ulna, Cymbella silesiaca and Gomphonema parvulum, were frequent1 y found in large numbers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the some studies, it is stated that C. cymbiformis var. nonpunctata (Figure 3, m) was previously found by Şahin (1998), Sıvacı and Pabuçcu (2007), Baytut and Gönülol (2016). However, none of the previous studies are on sediment cores and in none of them has been found in fossil records.…”
Section: Resultsmentioning
confidence: 66%
“…In the some studies, it is stated that C. cymbiformis var. nonpunctata (Figure 3, m) was previously found by Şahin (1998), Sıvacı and Pabuçcu (2007), Baytut and Gönülol (2016). However, none of the previous studies are on sediment cores and in none of them has been found in fossil records.…”
Section: Resultsmentioning
confidence: 66%
“…In Turkey, studies of diatom were began by Yıldız in Meram stream [7] and followed by other researchers which mostly concentrated on various physicochemical factors affecting the development of diatoms in addition to their flora in cental anatolian [9,10,11,12,13,14,15,16]. In recent years, some topics that determine trophic state and water quality level of a stream monitoring by means of diatom indices based on the variety and density of the diatoms in water or on the substrat have become popular [17,18,19].…”
mentioning
confidence: 99%